Application of Metres for Sentimental Purposes in Sanskrit Literature: : With References to Sanskrit Play Entitled Ratnāvalī of King Śrī Harṣavardhana - Kongmebhol, Aroonwan (Journal of Letters, 2025)
Currently, research on the relationship between metres (chandas) and literary sentiments (rasa) in classical Sanskrit poetry is quite meagre. This research aims to investigate the application of metres for sentimental purposes in Sanskrit play entitled Ratnāvalī of King Śrī Harṣa Vardhana. The research subject highlights selected thirteen stanzas, each of which the sentiment is apparent, from the Ratnāvalī. The methodology of the research consists of a textual translation from Sanskrit to Thai as well as an analysis on the literary sentiments, the schemes of metres, including properties of vowels and consonants used in the metres. The research framework is founded upon Nāṭyaśāstra, particularly sections involving metres and sentiments. The study found that the metrical stanzas most frequently convey Śṛṅgāra Rasa (erotism), followed by Karuṇa Rasa (pathos), Adbhuta Rasa (wonder), Rāudra Rasa (anger), Vīra Rasa (heroism) and Bhayānaka Rasa (horror) respectively. The metrical form of each verse varies in nature, i.e., the total number of syllables, the difference between short and long syllables (laghu and guru), the rhythm, and frequency of these syllables. These features significantly correlate with the expression of rasa. Additionally, the qualities of vowel and consonant sounds used in the verses contribute to the melodiousness and poetic appreciation. All of these elements align with the principles of Nāṭyaśāstra. It could be said that while considering the relationship between the rhythms of the metres and the emotions expressed in the poetry, King Śrī Harṣa Vardhana deliberately applied specific metres to some particular stanzas.